Implementation of Theoretical Study of Situational Leadership Style at the Ministry of Religion Office Institution in Serang Regency - Rohaemi; Fakhriy Falah; Anis Fauzi; Anis Zohriah (al-Afkar, Journal For Islamic Studies, 2025)
The situational leadership style is a unique style that can be applied in various conditions. This leadership style has an important role in that a leader must be able to adapt to various levels of maturity of both individuals and groups in different situations and conditions, to produce flexible and efficient behavior. Leadership is an ability inherent in a leader, which is influenced by various factors, both internal and external. The leader's ability must be able to influence, motivate, inspire, direct and coach employees in achieving the goals that have been set. This research uses a qualitative research method based on a literature review known as a literature review. while the research subject in this method discusses the application of theoretical studies of situational leadership styles in the Ministry of Religion office in Serang district. This aims to clarify and make it easier to explain and convey the main points of research. The research data sources were obtained from journals and articles and writings related to the research subject via mendeley.com, the publish or perish application and Google Scholar. So the research results show that by using 4 (four) styles in leadership, namely; Intuition, consultation, participation and delegation styles have a big influence on employee performance in an institution or company where effective and efficient leader behavior will always provide support and guidance to employees in developing themselves from not understanding to understanding so that leaders can achieve their leadership goals well.